The Impact of The Russia-Ukraine Conflict On International Relations - Roby Arman Myajaya (International Forum of Researchers and Lecturers, 2024)
This study explores the international impact of the Russia-Ukraine conflict, focusing on its economic, political, and security dimensions. Economically, the conflict has disrupted global supply chains, especially in energy and agricultural sectors, causing price volatility and inflation worldwide. Politically, it has reshaped international alliances, with Western countries reinforcing NATO and imposing sanctions on Russia, while other nations maintain neutrality or align strategically. In the security sphere, the conflict has heightened tensions between major powers and triggered increased military spending globally. The study employs a qualitative method using a literature review approach, analyzing primary and secondary sources such as policy documents, academic articles, and international reports. Recommendations include strengthening multilateral diplomacy to mediate the conflict and addressing the cascading economic and security effects through international cooperation. The study concludes that mitigating the impact of the Russia-Ukraine conflict requires comprehensive strategies that balance geopolitical interests and global stability.